T‐cell immune response after mRNA SARS‐CoV‐2 vaccines is frequently detected also in the absence of seroconversion in patients with lymphoid malignancies - Marasco, Vincenzo; Carniti, Cristiana; Guidetti, Anna; Farina, Lucia; Magni, Martina; Miceli, Rosalba; Calabretta, Ludovica; Verderio, Paolo; Ljevar, Silva; Serpenti, Fabio; Morelli, Daniele; Apolone, Giovanni; et al. (British journal of haematology, 2022)
Summary Patients affected by lymphoid malignancies (LM) are frequently immune‐compromised, suffering increased mortality from COVID‐19. This prospective study evaluated serological and T‐cell responses after complete mRNA vaccination in 263 patients affected by chronic lymphocytic leukaemia, B‐ and T‐cell lymphomas and multiple myeloma. Results were compared with those of 167 healthy subjects matched for age and sex. Overall, patient seroconversion rate was 64·6%: serological response was lower in those receiving anti‐cancer treatments in the 12 months before vaccination: 55% vs 81·9% (P < 0·001). Anti‐CD20 antibody plus chemotherapy treatment was associated with the lowest seroconversion rate: 17·6% vs. 71·2% (P < 0·001). In the multivariate analysis conducted in the subgroup of patients on active treatment, independent predictors for seroconversion were: anti‐CD20 treatment (P < 0·001), aggressive B‐cell lymphoma diagnosis (P = 0·002), and immunoglobulin M levels <40 mg/dl (P = 0·030). The T‐cell response was evaluated in 99 patients and detected in 85 of them (86%). Of note, 74% of seronegative patients had a T‐cell response, but both cellular and humoral responses were absent in 13·1% of cases. Our findings raise some concerns about the protection that patients with LM, particularly those receiving anti‐CD20 antibodies, may gain from vaccination. These patients should strictly maintain all the protective measures.